PHOSPHAT ACID AND FLOCCULAN ADDED IN JUICE SUGAR CRYSTAL PROCESS - Suci Perwitasari, Dyah (Jurnal Teknik Kimia, 2010)
The level of the requirement would sugar increased continued each year, in line with thegrowth and the development of the inhabitants as well as technology in Indonesian. To overcomethis lack, a part from with did import sugar was also done by the increase in the sugar industrycame from palm juice sugar. Palm juice sugar was the only main raw material in the productionof crystal sugar for the moment. For produced clear palm juice with the better quality, then mustbe paid attention to by the age, the maturity, the kind, the freshness from the sugar cane croppersonally. The aim of this research was to look for the alternative to the replacement from theprocess sulfitasi that uptil now was worn the sugar factory and to know the optimal condition fromclear palm juice by seeing the dose floculan in accordance with the condition that was undertaken.The process of his research of being raw palm juice was increased lime milk until the alkalinecondition and was heated until the temperature 100 oC, After wards was added by use phosphateacid as the condition that was determined and floculan in accordance with the variable that wasundertaken. Further was bent, refined and analysed. Best results were obtained palm juice withthe increase in phosphat acid the dose 80 mg/l and without floculan that is 91.37 oS; whereas forthe analysis of the content phosphat, turbidy, the colour and the content of the lime were 31,8 mg/l,14,8 mg/l, 2749 ICU, 483 mg/l that is in the increase in the dose of phosphate acid 80 mg/l andfloculan 2 mg/l.Keywords :Phosphat acid, floculan, palm juice sugar.